Kant's Criticism of Common Moral Rational Cognition. (29th December 2016) - Sticker, Martin
Abstract: There is a consensus that Kant's aim in the Groundwork is to clarify, systematize and vindicate the common conception of morality. Philosophical theory hence serves a restorative function. It can strengthen agents' motivation, protect against self‐deception and correct misunderstandings produced by uncritical moral theory. In this paper, I argue that Kant also corrects the common perspective and that Kant's Groundwork shows in which senses the common perspective, even considered apart from its propensity to self‐deception and without being influenced by misleading theory, is deficient. Critical practical philosophy needs to set right agents about the stringency of some of their duties, and agents need to be made aware that they have certain other duties. I discuss how Kant corrects the common agent's notion of the stringency of the duty to not make false promises and how Kant corrects the common agent's notion of duties to self. I finally discuss how his critical practical philosophy can become popular and achieve the correction of the common perspective. I stress the role of education informed by philosophical theory for this and contrast it with so called 'popular philosophy'.